R Visualizations: Derive Meaning from Data - Gerbing, David W. (CRC Press, 2020)
This book shows how to do data visualization using the R data analysis language. The emphasis is on how to, with examples from many R packages across a wide range of visualizations. The book features both a review of the highly capable ggplot2 visualization package, as well as a rethinking of how to do data visualization with the author's lessR package.